Empirical Correlation of Shear Wave Velocity And N-Spt Value for Jakarta - Achmad Fauzi, Abdul Wahab; Irsyam, Masyhur; Fauzi, Usama Juniansyah (GEOMATE International Society, 2014)
This paper proposes an equation representing shear wave velocity (Vs) as a function of SPT blow count (N-SPT). The equation is generated by statistical regression of site investigation data at many building project in Jakarta. The N-SPT values and Vs values were obtained from the same boreholes between 2005 and 2012. The Vs values were obtained by the downhole seismic survey. A total of 22 building and 35 borings provided 234 pairs of N-SPT and Vs values were used to get a regression equation. The new and previously suggested formulae have been compared and evaluated by using the same dataset. Wave propagation analysis require Vs as an input parameter, and the empirical equation may be useful for estimating Vs at site where only N-SPT data available. The information of empirical correlation can and perhaps should be considered in developing microzonation map of Jakarta as inputs in a continuous process of risk assessment and disaster mitigation risk reduction.